Pembatalan Perkawinan Tanpa Persetujuan Orang Tua sebagai Wali Nasab (Studi Putusan Pengadilan Agama Medan No. 2530/Pdt.G/2019/PA.Mdn) - Devia Sutanri Nasution; Hasballah Thaib; Zamaksyari Bin Hasballah Thaib (Inovasi Pratama Internasional. Ltd, 2022)
The problem of this research, related to marriage without the consent of the guardian of the lineage can be canceled. legal consequences after the marriage was annulled without the permission of the lineage guardian and the judge's legal considerations in the Medan Religious Court Decision No. 2530/Pdt.G/2019/PA.Mdn. This study uses literature research and empirical research at the Medan Religious Court by conducting interviews with two judges. The results of the study that marriages without the consent of the nasab guardian can be canceled, this is in accordance with the provisions of Article 22 of Law Number 1 of 1974 which states